Selective Neurectomy for Treatment of Post-Facial Paralysis Synkinesis: A Systematic Review - Shikara, Meryam; Bridgham, Kelly; Ludeman, Emilie; Vakharia, Kalpesh; Justicz, Natalie (Facial Plastic Surgery, 2022)
Background Synkinesis is commonly encountered after flaccid facial paralysis and can have a detrimental impact on a patient's life. First-line treatment of synkinesis is chemodenervation with botulinum toxin (Botox) and neuromuscular retraining. Surgical options include selective myectomy, selective neurectomy (SN), cross-facial nerve grafting, nerve substitution, and free gracilis muscle transfer. Data on surgical management of synkinesis using SN is limited.Evidence Review PubMed, Embase, Cochrane CENTRAL, Cochrane Neuromuscular Register, Clinicaltrials.gov, and World Health Organization International Clinical Trials Registry Platform were searched using a comprehensive keyword strategy in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. All English-only texts published in the past 20 years were included. Two independent investigators reviewed 906 abstracts and 7 studies met inclusion criteria. Demographics, etiology of paralysis, time to surgery, and primary outcomes studied were collected.Findings A total of 250 patients were included across 7 studies. In 6 out of 7 studies, Botox was used prior to surgical intervention. Two studies showed significant reduction in Botox dosage postoperatively, while one study showed no difference. Other primary outcomes included the House–Brackmann Score, palpebral fissure width, electronic clinician-graded facial function scale (eFACE) score, Facial Clinimetric Evaluation (FaCE) scale, and Synkinesis Assessment Questionnaire (SAQ). Three studies showed significant improvement in the eFACE score, two studies showed significant improvement in the FaCE scale, while one study showed improvement in quality of life measured by the SAQ.Conclusion SN can be considered as an adjunct to other management options including neuromuscular retraining, Botox, selective myectomy, and reanimation procedures. While there is great heterogeneity of study design in the studies included, many cohorts showed improvement in facial symmetry, facial function, and quality of life. There remains a great gap in knowledge in this subject matter and a need for large well-designed prospective studies comparing this technique to other management options.
Keywords: nonflaccid facial paralysis; facial synkinesis; post-facial paralysis synkinesis; selective neurectomy; modified selective neurectomy